Is the oocyte quality affected by endometriosis? A review of the literature - Ana Maria Sanchez; Valeria Stella Vanni; Ludovica Bartiromo; Enrico Papaleo; Eran Zilberberg; Massimo Candiani; Raoul Orvieto; Paola Viganò (BMC, 2017)
Abstract Endometriosis is an estrogen-dependent chronic inflammatory condition that affects women in their reproductive period causing infertility and pelvic pain. The disease, especially at the ovarian site has been shown to have a detrimental impact on ovarian physiology. Indeed, sonographic and histologic data tend to support the idea that ovarian follicles of endometriosis patients are decreased in number and more atretic. Moreover, the local intrafollicular environment of patients affected is characterized by alterations of the granulosa cell compartment including reduced P450 aromatase expression and increased intracellular reactive oxygen species generation. However, no comprehensive evaluation of the literature addressing the effect of endometriosis on oocyte quality from both a clinical and a biological perspective has so far been conducted. Based on this systematic review of the literature, oocytes retrieved from women affected by endometriosis are more likely to fail in vitro maturation and to show altered morphology and lower cytoplasmic mitochondrial content compared to women with other causes of infertility. Results from meta-analyses addressing IVF outcomes in women affected would indicate that a reduction in the number of mature oocytes retrieved is associated with endometriosis while a reduction in fertilization rates is more likely to be associated with minimal/mild rather than with moderate/severe disease. However, evidence in this field is still far to be conclusive, especially with regards to the effects of different stages of the disease and to the impact of patients' previous medical/surgical treatment(s).